Strategies for Securing Key Raw Materials for Secondary Batteries through Battery Recycling: Case Studies on Battery Materials and Manufacturing Companies (aSSIST Business Review, 2026)
Background/Purpose: The rapid growth of electric vehicles (EVs) and energy storage systems (ESS) has driven explosive demand for secondary batteries. Key raw materials—lithium, nickel, and cobalt—face mounting supply-chain risks and resource-depletion concerns, making sustainable procurement strategies an urgent priority. This study explores how battery recycling can ensure a stable supply of these critical materials and proposes practical strategies derived from leading-company case analyses. Study Design/Methodology/Approach: A qualitative, multi-case study methodology was applied, examining three global recycling leaders—SungEel HiTech, Ecopro, and Umicore—alongside four intercompany collaboration cases (Samsung SDI–SungEel HiTech; Ultium Cells–Li-Cycle; CATL–Volvo; Japan–EU). Data were gathered from corporate disclosures, industry association reports, and media coverage through 2024. Findings: Each firm leverages distinct technical capabilities to recover high-value metals from spent batteries. SungEel HiTech operates an integrated pre- and post-treatment system targeting high-purity metal recovery. Ecopro maximises efficiency through a closed-loop eco-system linking lithium hydroxide, precursor, cathode, and recycling stages. Umicore combines pyrometallurgical and hydrometallurgical processes to maximise recovery rates while pursuing ESG-aligned innovation. Cross-company collaborations demonstrate that supply-chain partnerships are essential for economic viability. The global end-of-life battery market is projected to grow from approximately 44 GWh (2025) to 338 GWh (2030) and 1,329 GWh (2040). Originality/Value: This study provides a structured 4-company/4-collaboration analysis of battery recycling strategies in a rapidly evolving regulatory landscape (EU Battery Regulation, US Recycling and Environmentally Friendly Battery Act), offering actionable strategic and policy insights for industry practitioners and policymakers seeking to advance the secondary battery circular economy.
Keywords: battery recycling; secondary battery; lithium; nickel; cobalt; circular economy; end-of-life battery; supply chain; SungEel HiTech; Ecopro; Umicore